Measurement of the Top Quark Mass Using Events With a Single Reconstructed Top Quark in Pp Collisions at Root S=13 Tev - Karapınar, Güler; Karapınar, Güler (Springer, 2021)
A measurement of the top quark mass is performed using a data sample enriched with single top quark events produced in the t channel. The study is based on protonproton collision data, corresponding to an integrated luminosity of 35.9 fb(-1), recorded at root s = 13TeV by the CMS experiment at the LHC in 2016. Candidate events are selected by requiring an isolated high-momentum lepton (muon or electron) and exactly two jets, of which one is identified as originating from a bottom quark. Multivariate discriminants are designed to separate the signal from the background. Optimized thresholds are placed on the discriminant outputs to obtain an event sample with high signal purity. The top quark mass is found to be 172.13(-0.77)(+0.76) GeV, where the uncertainty includes both the statistical and systematic components, reaching sub-GeV precision for the first time in this event topology. The masses of the top quark and antiquark are also determined separately using the lepton charge in the final state, from which the mass ratio and difference are determined to be 0.9952(-0.0104)(+0.0079) and 0.83(-1.35)(+1.79) GeV, respectively. The results are consistent with CPT invariance.
Keywords: Hadron-Hadron scattering (experiments)